Conceptual ClusteringAnalysis in Data Mining: A Study - Nikhila, K.; Manvitha, P. (International Journal of Engineering and Technology, 2018)
Clustering on unsupervised learning handles with instances, which are not classified already and not having class attribute with them. Applying algorithms is to find useful but items on unknown classes. Approach of unsupervised learning is about instances are automatically making into meaningful groups basing on its similarity. This paper we study about the basic clustering       methods in data mining on unsupervised learning such as ensembles distributed clustering and its algorithms.